THE USE OF BOARD RACE GAME IN IMPROVING STUDENTS' VOCABULARY MASTERY AT SECOND GRADE OF TSANAWIYAH BABUL KHAER BULUKUMBA - Pratiwi, Widya Rizky; Nur, Muhammad Agus (Fakultas Keguruan dan Ilmu Pendidikan, 2019)
Vocabulary is the heart of a language because it involves the basic building of English sentences. Without a meaningful vocabulary, the four basic skills of language namely speaking, listening, reading, and writing would never be complete. As vocabulary is the principal issue for English learning, this current research was conducted to see the effectiveness of the Board Race Game to improve the students’ mastery of vocabulary. The research was conducted in Tsanawiyah Babul Khaer, Bulukumba. There were 30 students of the second grade in the academic year 2018/2019 who participated in this study which was selected through purposive sampling. In collecting the data, the researchers used the pre and post design of the experimental group. The researchers analyzed the average score of each test to find out the increase in students’ vocabulary mastery after the action was conducted. After the researchers have treated the game in four meetings, the students’ vocabulary mastery has increased significantly. It could be seen from the score of pre-test was 30,46 and the posttest was 78,2 where the gain of both tests was 47,73. After applying the action, the researchers were able to solve the problem in increasing students’ vocabulary mastery. Thus, because of this kinesthetic game was successfully to create a fun atmosphere in the teaching and learning process and increase the students’ mastery of vocabulary, it is suggested to use board race game as the alternative media in teaching English.